Global Development of Community Colleges and Further Education Programs - Gaulee, Uttam (Journal of Interdisciplinary Studies in Education, 2019)
For someone with general interest and background in the internationalization of higher education and as a member of an independent policy forum working with community college in America, I was pleased to see this volume promising a useful resource for anyone working in the field. The community college is an American innovation in higher education and economics. By creating access to real economic opportunities for a large number of young men and women with increased educational attainment, the community college reduced income inequality (Brown, 2012). By focusing on multiple constituencies within the community, community colleges identified the community needs and provided increased opportunities for education for